New Mitotic Regulators Released from Chromatin - Yokoyama, Hideki; Gruss, Oliver (Frontiers in Oncology, 2013)
Faithful action of the mitotic spindle segregates duplicated chromosomes into daughter cells. Perturbations of this process result in chromosome mis-segregation, leading to chromosomal instability and cancer development. Chromosomes are not simply passengers segregated by spindle microtubules but rather play a major active role in spindle assembly. The GTP bound form of the Ran GTPase (RanGTP), produced around chromosomes, locally activates spindle assembly factors. Recent studies have uncovered that chromosomes organize mitosis beyond spindle formation. They distinctly regulate other mitotic events, such as spindle maintenance in anaphase, which is essential for chromosome segregation. Furthermore, the direct function of chromosomes is not only to produce RanGTP but, in addition, to release key mitotic regulators from chromatin. Chromatin-remodeling factors and nuclear pore complex proteins, which have established functions on chromatin in interphase, dissociate from mitotic chromatin and function in spindle assembly or maintenance. Thus, chromosomes actively organize their own segregation using chromatin-releasing mitotic regulators as well as RanGTP.